Simultaneous detection and evaluation of Prevotella intermedia, Prevotella nigrescens, Prevotella loescheii, and Prevotella melaninogenica in subgingival plaque samples of chronic periodontitis and healthy individuals through multiplex polymerase chain reaction - Vijaylakshmi S Kottrashetti; Kishore G Bhat; Manohar S Kugaji; Sachita Shrikant Naik; Praveen Tanakanti (Wolters Kluwer Medknow Publications, 2023)
Background: Prevotella is a Gram-negative anaerobic bacilli. The phenotypic characteristics of the various species of Prevotella are similar, which often makes it difficult in routine differentiation and identification of all the species. Aim: The purpose of the study was to detect and compare presence of Prevotella intermedia, Prevotella nigrescens, Prevotella melaninogenica, and Prevotella loescheii in subgingival plaque samples of chronic periodontitis and healthy individuals. Materials and Methods: Two hundred and thirty-six subjects were considered consisting of chronic periodontitis (128) and healthy (108) individuals. Subgingival plaque sample was collected in reduced transport fluid and analyzed. DNA extraction and polymerase chain reaction (PCR) were performed for genus Prevotella followed by positive samples were considered for the detection of selected species through multiplex PCR using specific primers. Results: Out of 236 samples, 94.1% were positive for genus Prevotella. Out of 222 cases P. nigrescens showed the highest number of cases positive (59.5%) followed by P. melaninogenica (57.2%), P. intermedia (55.4%), and P. loescheii (40.1%). Species were analyzed individually between chronic periodontitis and healthy, P. intermedia, P. nigrescens, and P. loescheii showed greater positivity in healthy compared to chronic periodontitis. Positivity for P. melaninogenica was high in chronic periodontitis compared to healthy. Conclusion: The number of positive cases for species, when correlated with clinical parameters showed an increase in mean score for all clinical parameters assessed, suggesting the presence of variation in the prevalence of Prevotella species and geographic variation do exist in oral microflora. Findings suggest that they can be normal commensals and opportunistic.